Blood pressure phenotypes based on ambulatory monitoring in a general middle-aged population. (4th July 2021) - Lin, Yi-Ting; Lampa, Erik; Fall, Tove; Engström, Gunnar; Sundström, Johan
Abstract: Background: Ambulatory blood pressure monitoring (ABPM) is increasingly recommended for clinical use, but more knowledge about the prevalence and variability in ABPM-derived phenotypes in the general population is needed. We describe these parameters in the community-based Swedish CArdioPulmonary bioImage Study (SCAPIS) cohort. Methods: We examined 5881 men and women aged 50–64 with 24-hour ABPM recordings using validated monitors. ABPM phenotypes were defined according to European guidelines. White coat hypertension was defined as elevated office BP (≥140/90 mmHg) with normal mean ambulatory BP (<135/85 mmHg in day-time, <120/70 mmHg in night-time, <130/80 mmHg over 24-h); and masked hypertension as normal office BP (<140/90 mmHg) with elevated mean ambulatory BP (≥135/85 mmHg in day-time, ≥120/70 mmHg in night-time, ≥130/80 mmHg over 24-h). Blood pressure variability was assessed using the coefficient of variation (CV), standard deviation (SD), and average real variability. Results: Based on the ABPM recordings, 36.9% of participants had 24-h hypertension, 40.7% had day-time hypertension, and 37.6% nocturnal hypertension. Among participants treated with anti-hypertensive drugs, one in three had elevated office blood pressures, and more than half had elevated 24-h, day-time or nocturnal blood pressures. Among participants without anti-hypertensive drugs, only one in six had elevated office blood pressures, but one in three had elevated 24-h, day-time or nocturnal blood pressures. Men had higher 24-h blood pressures, more masked hypertension, but less white-coat hypertension than women. The prevalence of white-coat hypertension increased with age, but not the prevalence of masked hypertension. A positive association between blood pressure level and variability was observed, and within-person and between-person SD and CV were of similar magnitude. The variance in ABPM on repeated measurements was substantial. Conclusions: In the middle-aged general population, masked hypertension is an underappreciated problem on the population level.